Research on the integration of labor education and ideological and political education in colleges and universities in the new era - Rong, Gui (International Journal of Social Sciences and Public Administration, 2024)
As an important part of the socialist education system with Chinese characteristics, labor education and ideological and political education are the central tasks of school education, with moral cultivation as its fundamental goal and important mission. Ideological and political education plays the role of ideological guidance in the process of labor education, and labor education can concretely realize the goal of ideological and political education and promote the mutual promotion of students' ideological and political education and the sense of labor acquisition. Facing the new requirements, new opportunities and new challenges of the new era, strengthening the integration of labor education and ideological and political education is an important way to strengthen and improve the ideological and political work in colleges and universities, improve the labor quality of college students, and train qualified talents who meet the needs of society.